A comparative study of Dashamoola Taila Matra Basti and Tila Taila Matra Basti in Kashtartava (dysmenorrhea) - Karunagoda, Kaumadi (Medknow Publications Pvt Ltd, 2010)
Kashtartava is a broad term which covers all the problems and ailments that a woman may suffer from during or around menstruation. It includes both primary and secondary types of dysmenorrhea. For this study, however, we considered only primary dysmenorrhea under the term Kashtartava to cover a larger population and to make a pin-pointed assessment criteria. Thus, 40 patients in the age-group of 15–25 years suffering from primary dysmenorrhea were registered for the study. Of these patients, 35 completed the course of treatment. The selected patients were randomly allotted into two groups. Group A received Dashamoola Taila Matra Basti and group B received Tila Taila Matra Basti. These treatments were selected for the Vatashamaka, Yonishula Prashaman, and Shothahara properties of the drugs. The dose was 60 ml per day and the duration of treatment was for 7 days each cycle for two consecutive cycles. Results were assessed according to a specially prepared grading system for pain, Alpartava, Yatochitkaladarshana, Praseka, Chhardi, Vibandha, Shrama, Atisara, Vankshana, Kati, Janu Shula, Shiroshula, Swedadhikya, and Tamodarshana. Significant improvement was seen in symptoms in both groups, and on comparing the results in the two groups we found that the results were almost equivalent. There was complete remission of symptoms in 38.89% in group A and in 35.39% in group B, while there was marked improvement in 50% in group A and 47.65% in group B. However, there was a marked difference between the two groups with regard to recurrence of symptoms during the follow-up period of 2 months, with recurrence being significantly more in group B. The study suggests that Matra Basti can be a reliable treatment for relieving the symptoms of primary dysmenorrhea. We recommend that more research be done to confirm the findings of this study.